Educational books published by young Turks in Egypt (1890-1908) - Gunduz, Mustafa (Elsevier Science Bv, 2010)
In the process of modernization of the Ottoman Empire, Cairo has become one of the most important intellectual centers. In this process Ottoman intellectuals closely involved with the state's educational problems. They have written booklets to enlighten and educate the public. In these publications in order to get rid of the state that Ottoman Empire in it had been persistently emphasized primarily to strike into education. In these publications to understand the western classics fully the information which related to women's education, agriculture and industry have been asked to tell the public. In this paper, four books will be examined that related to public education published in Egypt between 1880 - 1908. They are Two Hopes (Iki Emel), Awaking! Awaking! (Uyaninnz! Uyaniniz!), Sultans and Princes (Padisah ve Sehzadeler) and Soldier (Asker).
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: History of Ottoman and Turkish Education; Young Turks; Egyptian Press in Ottoman Period; Abdullah Cevdet; Ahmed Riza